2021
DOI: 10.18632/aging.203451
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular emboli relates to immunosuppressive tumor microenvironment and predicts prognosis in stage III colorectal cancer

Abstract: Background: Stage III colorectal cancer (CRC) patients experience varying degrees of prognosis even if receiving standard therapeutic regimes. Intravascular emboli (IVE), a type of vascular invasion, impacts the clinical outcome in CRC. In this study, we confirmed the role of IVE in predicting the prognosis of stage III CRC patients and characterized the tumor microenvironment (TME) of CRC with IVE. Methods: Data from 220 consecutive patients (cohort 1) with stage III CRC undergoing radical surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Many studies suggest that surgery is essential in treating distant metastases of cancers, such as colorectal cancer ( 37 ). In addition, many studies on other cancers, including pancreatic and colorectal cancer, demonstrated that the tumor microenvironment, especially the extracellular matrix, has been found to play an essential role in cancer metastasis, local recurrence, and chemotherapeutic drug resistance ( 38 , 39 ). Many potential drugs are used due to their ability to target the extracellular matrix, such as PEGPH20 (an enzyme that targets matrix hyaluronic acid), pegilodecakin (a PEGylated IL-10) ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies suggest that surgery is essential in treating distant metastases of cancers, such as colorectal cancer ( 37 ). In addition, many studies on other cancers, including pancreatic and colorectal cancer, demonstrated that the tumor microenvironment, especially the extracellular matrix, has been found to play an essential role in cancer metastasis, local recurrence, and chemotherapeutic drug resistance ( 38 , 39 ). Many potential drugs are used due to their ability to target the extracellular matrix, such as PEGPH20 (an enzyme that targets matrix hyaluronic acid), pegilodecakin (a PEGylated IL-10) ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%